Justice, Peace and Political Dissent from the Early Middle Ages to the Communal Period (Italian Review of Legal History, 2017)
The ‘institutional’ affairs that unfolded between the early and late Middle Ages can be (and have been) reconstructed in varying degrees of detail through diplomas, documents and chronicles. Regarding Italy, there is also another source that up to now has been rather ignored, and which might offer some insight into the more strictly legal aspects of these events. Specifically, I am referring to eleventh-century Italian jurisprudence on political crimes. Indeed, legal stances on the repression of dissent, on the justification of resistance to authority and on making peace between ‘private’ parties can be found in the Expositio to the Liber Papiensis, in the legal formulary and in some glosses appearing in manuscripts which were still in use in the 1130s.These sources shed light on the expression and organization of political struggle in the Kingdom of Italy – be it through rebellion, protest or association – and on how that was perceived by the legitimate authorities. By studying them, it is possible to analyze how the concept of justice and institutions evolved from the early Middle Ages to the communal period.
Keywords: Expositio ad librum papiensem; political crime; resistance; private peace; commune cities